2018
DOI: 10.3390/f9010005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Net Primary Productivity and Forest Stand Age under Different Site Conditions and Its Implications for Regional Carbon Cycle Study

Abstract: Net primary productivity (NPP) is a key component in the terrestrial ecosystem carbon cycle, and it varies according to stand age and site class index (SCI) for different forest types. Here we report an improved method for describing the relationships between NPP and stand age at various SCI values for the main forest types and groups in Heilongjiang Province, China, using existing yield tables, biomass equations, and forest inventory data. We calculated NPP as the sum of four components: Annual accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…While at the fine scale, similar factors control the macroscopic patterns of biodiversity, the habitat selection by species is controlled primarily by biophysical and climatic factors [40,41]. However, the correlation between these factors and NPP is low because of the similar macroscopic biogeography conditions [42]. Therefore, at present, the interrelationship between vegetation productivity, biodiversity, and regulating ecosystem services is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…While at the fine scale, similar factors control the macroscopic patterns of biodiversity, the habitat selection by species is controlled primarily by biophysical and climatic factors [40,41]. However, the correlation between these factors and NPP is low because of the similar macroscopic biogeography conditions [42]. Therefore, at present, the interrelationship between vegetation productivity, biodiversity, and regulating ecosystem services is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The biomass-age relationship has been a widely used method for estimating forest BCS at the national and regional scales [21,24,52,53]. Early studies indicated that the biomass-age relationship could be described using a logistic [24,54], Richards [55,56] or Korf [43] function. It is hard to establish biomass-age relationships using a uniform expression at present.…”
Section: Methodology For Forest Bcs Estimationmentioning
confidence: 99%
“…Fitting the biomass-age relationship Statistical analysis is commonly used to fit the biomass-age relationship. Widely used regression models include Gompertz, Logistic, Korf, Mitscherlich, and Richards growth functions [22,43]. Previous studies have reported that biomass-age relationships greatly change through environmental gradients and among different forest types [21,24].…”
Section: Calculation Of Forest Bcsmentioning
confidence: 99%
“…The sum of autotrophic respiration and NPP is gross primary productivity (GPP). GPP is a parameter that is not directly measured and also measurement of autotrophic respiration is laborious (Gower et al, 1999;Berberoğlu et al, 2007;Ardö, 2015;Chen et al, 2016;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%